2015
DOI: 10.1186/s11671-015-1116-8
|View full text |Cite
|
Sign up to set email alerts
|

Strain Localization in Thin Films of Bi(Fe,Mn)O3 Due to the Formation of Stepped Mn4+-Rich Antiphase Boundaries

Abstract: The atomic structure and chemistry of thin films of Bi(Fe,Mn)O3 (BFMO) films with a target composition of Bi2FeMnO6 on SrTiO3 are studied using scanning transmission electron microscopy imaging and electron energy loss spectroscopy. It is shown that Mn4+-rich antiphase boundaries are locally nucleated right at the film substrate and then form stepped structures that are approximately pyramidal in three dimensions. These have the effect of confining the material below the pyramids in a highly strained state wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Another plausible explanation is that these atomic layers originate from an outward migration of the lower BiO planes due to the volatility of Bi. It should also be noted that similar structure with elongated lattice parameters occur in the form of antiphase boundary in doped BFO [28,29] , which suggests that these surface monolayers might be nucleation sites during growth. If more FeO 2 is added, this transient state would become proper BFO.…”
mentioning
confidence: 87%
“…Another plausible explanation is that these atomic layers originate from an outward migration of the lower BiO planes due to the volatility of Bi. It should also be noted that similar structure with elongated lattice parameters occur in the form of antiphase boundary in doped BFO [28,29] , which suggests that these surface monolayers might be nucleation sites during growth. If more FeO 2 is added, this transient state would become proper BFO.…”
mentioning
confidence: 87%
“…Below this APB, the film is highly strained, while above it, it is relaxed and close to the bulk state. 25 Besides Nd nanorods formed through exsolution, 26,27 Ti-rich APBs are formed in Nd-and Ti-codoped BFO separating tetragonal distorted regions with strong polar ordering at each side of the defect. 28 Similar structures have been reported in other BFO-based systems.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite oxides display abundant interfacial defects, e.g., domain walls and antiphase boundaries, due to their chemical and structural flexibility. Benefitting from the advanced atom-resolved characterizations via transmission electron microscopy (TEM) or atomic force microscopy, it is found that the interfacial defects are not only simple structural boundaries separating adjacent regions with different crystal structures or crystallographic orientations but also act as functional entities for exploring emergent phenomena caused by local symmetry breaking. Notable examples include domain wall-localized free electron gas in ferroelectric BaTiO 3 , unusual electronic transport behavior and novel photovoltaic charge separation in multiferroic BiFeO 3 , and ferroelectric dipole ordering in paraelectric CaTiO 3 . , Unlike fixed heterointerfaces, these homogeneous interfacial defects are more flexible, which can be controlled by external stimulants and/or chemical composition. An antiphase boundary can be generated from the well-defined substrate steps in a La 2/3 Sr 1/3 MnO 3 thin film grown on Sr 2 RuO 4. Twin boundaries are produced by thermomechanical treatment on a BaTiO 3 /Pt film .…”
Section: Introductionmentioning
confidence: 99%